Faktor-Faktor yang Memengaruhi Niat Membeli Produk Sustainable Skincare pada Generasi Z di Jabodetabek - Azahra Putri Dewi Mumpuni; Ryna Parlyna; Inkreswari Retno Hardini (Indo Publishing, 2026)
This study was motivated by the growing trend of sustainable lifestyles, particularly among Generation Z, which has increased interest in sustainable skincare products. However, this trend is not reflected in the Indonesian skincare market, where non-sustainable brands continue to dominate. This phenomenon indicates that increased awareness of sustainability does not necessarily lead to a higher intention to purchase sustainable skincare products. Therefore, this study was conducted to identify the factors influencing consumers' purchase intention toward sustainable skincare brands. The objective of this study is to examine the partial effects of social media marketing, brand awareness, brand image, and brand trust on purchase intention. A quantitative research approach was employed using a survey method, with data collected through a Google Forms questionnaire. The study involved 250 Generation Z respondents, born between 1997 and 2012, residing in Jakarta, and familiar with the brand From This Island. The collected data were analyzed using IBM SPSS Statistics Version 27. The findings indicate that social media marketing, brand awareness, brand image, and brand trust each have a positive and significant partial effect on purchase intention.